Dual asparagine-depriving nanoparticles against solid tumors - Yubo Shen; Huifang Wang; Daoxia Guo; Jiantao Liu; Jinli Sun; Nan Chen; Haiyun Song; Xiaoyuan Ji (Nature Communications)
Abstract Depletion of circulatory asparagine (Asn) by L-asparaginase (ASNase) has been used for clinical treatment of leukemia, whereas solid tumors are unresponsive to this therapy owing to their active Asn biosynthesis. Herein, we develop a type of core-shell structured cascade-responsive nanoparticles (NPs) for sequential modulation of exogenous Asn supply and endogenous Asn production. The reactive oxygen species-sensitive NP shells disintegrate in the tumor microenvironment and liberate ASNase to scavenge extracellular Asn. The acid-labile NP cores subsequently decompose in the tumor cells and release rotenone to block intracellular Asn biosynthesis. Administration of the dual Asn-depriving NPs in murine models of triple-negative breast cancer and colorectal cancer substantially suppress the growth and epithelial-mesenchymal transition of primary and relapsed tumors, fully eradicate spontaneous and post-surgical metastasis, and confer long-term T cell memory for complete resistance to tumor rechallenge. This study represents a generalized strategy to harness amino acid depletion therapy against solid tumors.